(untitled) (Polis (Santiago), 2018)
Economics as a social science, as a science of life, is being questioned on a daily basis due to the effects of a generalized logic of totalizing market that causes death and despair to increasingly larger groups of human beings; a logic that confronts and destroys the creation of subjects. A critical perspective is raised in response, an ethical point of view as well as attempts of multidisciplinary dialogue. In that sense, a research is being developed of which some is advanced in this text. The first part recovers the partial results of an inquiry –from a perspective of life-supporting ethics– regarding the reasons that attempt to explain the negation of the subject: from an economics’ point of view, from the perspective of postmodern thought and from the manipulation of desires and power. The second part includes analysis concerning criteria and options for the defense of the subject as a living subject, understanding him as subjectivity/intersubjectivity, which is not the same as individuality. The goal is to recover the foundation of human solidarity and an economic practice based on human rights.